Combining heavy flavour electroweak measurements at LEP - Dova, María Teresa (1996)
The ratios of cross sections, Rb = a(e+e- → bb)/a(e+e- → hadrons) and R, = cr(e+e- → E)/a(e+e- → hadrons) and , and the forward-backward asymmetries and , have been measured by the four LEP experiments at centre-of-mass energies close to the Z boson mass, using a variety of heavy flavour identification techniques and analysis methods. The procedure adopted to combine these measurements is described here. It takes into account the statistical and systematic correlations among the measurements and their interdependences in a χ2 minimization. The procedure is illustrated using published measurements.